High-temperature-resistant lubricant composition and preparation method thereof

Through the combination of modified nanoparticles and thickeners, the problem of inactivation of liquid lubricants at high temperatures is solved, and the high temperature and extreme pressure performance of the lubricant is improved, which extends the service life and reduces friction and wear.

CN119842430AActive Publication Date: 2025-04-18HUBEI BODA SPECIAL LUBRICANT CO LTD

Patent Information

Application Number
CN202510331844.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-18
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

Existing liquid lubricants are prone to volatilization, degradation and cross-linking under high temperature conditions, resulting in inactivation and failure of lubricating properties, and cannot effectively solve the problem of lubricant in drilling fluid.

Method used

The nanoparticles are modified by brominated-1-hexadecyl-3-methylimidazolyl ionic liquid, and combined with polyethylene glycol, modified polyurea grease and surfactant, to form a stable colloidal system to improve the dispersion and compatibility of the nanoparticles.

Benefits of technology

It significantly improves the high temperature and extreme pressure resistance of the lubricant, extends the service life of the grease, reduces the friction coefficient and wear, and enhances the lubricating effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of bearing lubricating grease, and particularly discloses a high-temperature-resistant lubricant composition and a preparation method thereof. The high-temperature-resistant lubricant composition comprises the following raw materials in parts by weight: 90-110 parts of base oil, 30-35 parts of a thickening agent, 2-3.5 parts of modified nanoparticles, 0.5-1.5 parts of an antioxidant, 1-3 parts of an antirust agent and 0.5-1 part of a friction modifier, the thickening agent comprises polyethylene glycol, modified polyurea lubricating grease and a surfactant according to a mass ratio of 1: (0.3-0.5): (0.1-0.15); the modified nano particles are brominated-1-hexadecyl-3-methylimidazolyl ionic liquid modified nano particles, and the nano particles comprise carbon nano particles and nano tungsten disulfide in a mass ratio of (2-3): 1. The lubricating grease composition provided by the invention has the advantages of good nanoparticle dispersibility, strong high temperature resistance, and excellent oxidation stability and antifriction and antiwear properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of bearing grease, and more specifically, to a high temperature resistant lubricant composition and a preparation method thereof. Background Art

[0002] As we all know, in the oilfield development industry, the lubricating properties of drilling fluids have a great impact on drilling work. Therefore, the lubricants used in drilling fluids are required to enable the drilling fluid to reduce the torque, wear and fatigue of the drill tools, extend the service life of the drill bit bearings, prevent adhesion and drill bit sticking, and reduce mud packing of the drill bit. Lubricants are a kind of treatment agent added to drilling, completion or fracturing fluids to improve the lubrication properties. Their main function is to reduce the torque, wear and abrasion of the drilling tools and their damage rate. Lubricants are divided into liquid and solid lubricants according to their phase state. Liquid lubricants mainly include mineral oils, vegetable oils, alcohol ethers, esters and nanomaterial lubricants. Solid lubricants mainly include plastic balls, glass balls, graphite and carbon black lubricants.

[0003] Deep wells and ultra-deep wells are in high-temperature environments. Existing liquid lubricants are prone to volatilization, degradation and cross-linking under high-temperature conditions, resulting in loss of activity and failure. Existing lubricants for high-temperature resistant drilling fluids, completion fluids, and fracturing fluids cannot effectively solve the problems of lubricant deactivation and failure.

[0004] In order to improve the high temperature resistance and extreme pressure wear resistance of lubricants, nanoparticles, such as inorganic nanoparticles with layered structures (graphite sheets, MoS2), soft metal nanoparticles (Cu, Pb), etc., are added to liquid lubricants to effectively reduce the friction coefficient of lubricants and improve their extreme pressure performance and load-bearing capacity. With respect to the above-mentioned related technologies, the inventors found that these nanoparticles used are added in a solid form, have poor compatibility with liquid lubricants, low extreme pressure performance and are easy to precipitate, thereby affecting the use effect of lubricants under high temperature and high pressure conditions. Summary of the invention

[0005] In order to improve the dispersibility and compatibility of nanoparticles in lubricants, reduce precipitation and stratification, and enhance high temperature and high pressure resistance, the present application provides a high temperature resistant lubricant composition and a preparation method thereof.

[0006] In the first aspect, the present application provides a high temperature resistant lubricant composition, which adopts the following technical solution: A high temperature resistant lubricant composition comprises the following raw materials in parts by weight: 90-110 parts of base oil, 30-35 parts of thickener, 2-3.5 parts of modified nanoparticles, 0.5-1.5 parts of antioxidant, 1-3 parts of rust inhibitor, and 0.5-1 part of friction modifier; The thickener comprises polyethylene glycol, modified polyurea grease and surfactant in a mass ratio of 1:0.3-0.5:0.1-0.15; The modified nanoparticles are bromide-1-hexadecyl-3-methylimidazolium-based ionic liquid modified nanoparticles, and the nanoparticles include carbon nanoparticles and nano-tungsten disulfide in a mass ratio of 2-3:1.

[0007] By adopting the above technical scheme, the nanoparticles are modified by using brominated 1-hexadecyl-3-methylimidazolium ionic liquid, and a thickener containing polyethylene glycol, modified polyurea grease and surfactant is added. The polyethylene glycol can form a protective film on the friction interface, effectively reducing the friction coefficient and reducing wear. The polyethylene glycol has high stability and can maintain stable lubrication performance under high temperature and high pressure. It also has strong oxidation resistance and corrosion resistance and can protect mechanical equipment from oxidation and corrosion. The dropping point of polyurea grease is usually as high as 250°C or above, and it can maintain lubricity in high temperature environment, is not easy to drip oil or coke, and can maintain its chemical stability even under high temperature conditions. Stability, effectively preventing problems such as high-temperature drying and friction, and its consistency will not change significantly when used for a long time in a high-temperature environment, maintaining good working performance, and has excellent antioxidant properties to resist oxidation reactions in a high-temperature environment and extend service life; surfactants can adjust the surface tension of polyethylene glycol and polyurea resin, improve the wetting, contact and diffusion between the two phases, and strengthen the interface bonding force; using polyethylene glycol and polyurea grease as thickeners can form a stable colloid system with the base oil, and the urea group (—NH—CO—NH—) in the polyurea molecule has strong polarity, and the molecules are combined with strong hydrogen bonds, making the entire colloid system in a very stable state. This stability helps the grease maintain its performance under harsh conditions such as high temperature and heavy load.

[0008] Nano tungsten disulfide is a new type of solid lubricating material with a layered hexagonal crystal structure. Since the bond energy of the six-element molecular bond between the layers is relatively low, it is easy to slip when friction occurs, so it has excellent tribological properties. In addition, nano tungsten disulfide has a small particle size, a large specific surface area and high diffusion performance, and is easy to adsorb on the metal surface, thereby improving the tribological properties of the lubricant composition, and can effectively reduce the friction factor of the bearing when working in a high temperature environment, reduce energy consumption, and reduce grease consumption, and extend the working life of the grease; Nano tungsten disulfide mainly relies on friction chemical reactions on the friction surface to generate a chemical reaction film to reduce friction and wear. In steel-steel friction, the formation process of this chemical reaction film is: under the action of friction heat, tungsten disulfide decomposes to generate W and sulfur anions (S 2-), then W diffuses and deposits on the metal surface, and at the same time S reacts with the base metal Fe to generate anti-wear and friction-reducing components such as FeS. This chemical reaction film not only organizes the direct contact between the friction surfaces, but also has a high load-bearing capacity, so that the elastic deformation and plastic deformation caused by shear stress are limited to the lubricating film area, thereby effectively inhibiting the adhesive wear and contact fatigue of the friction surface, playing a role in protecting the friction surface, and the thickness of the reaction film increases with the increase of the friction heating temperature, so under the action of high temperature, the lubrication effect of tungsten disulfide is better; Carbon nanoparticles have excellent chemical and thermal stability, low cost, and the inherent self-lubricating effect of carbon nanomaterials. In addition, the quasi-spherical shape and ultra-small particle size tend to eliminate the embedding stability barriers of traditional carbon nanomaterials in micro-convex friction interfaces, which is conducive to the carbon nanoparticles acting as ball bearings, filling the grooves on the friction surface, increasing the contact area, reducing the contact pressure, and enhancing the pressure resistance and extreme pressure performance under load and lubrication conditions.

[0009] Ionic liquids are room temperature molten salts that can be constructed by a flexible combination of cations and anions. The use of bromide-1-hexadecyl-3-methylimidazolium-based ionic liquids to modify nanoparticles can improve the dispersibility of nanoparticles in base oils such as polyethylene glycol. The bromide-1-hexadecyl-3-methylimidazolium-based ionic liquid can be used to coat the surface of nanoparticles to obtain uniformly dispersed ionic liquid-modified nanoparticles, thereby improving the dispersibility of nanoparticles in the base oil, enhancing their interfacial interaction with the base oil, and reducing the agglomeration and sedimentation of nanoparticles in the base oil. Since the alkyl chain-coated nanoparticles have high reactivity, they are further conducive to the formation of friction films under harsh lubrication conditions. In addition, the low-energy electrons emitted by the micro-bumps on the friction surface cause the friction interface to be positively charged. The long alkyl chain anions not only promote the dispersion of nanoparticles into the base oil, but also adsorb on the friction interface, thereby reducing friction and wear.

[0010] Optionally, the preparation method of the modified nanoparticles is as follows: The bromide-1-hexadecyl-3-methylimidazolium ionic liquid is mixed with chloroform, the temperature is raised to 40-50° C., and the mixture is stirred evenly. Then, carbon nanoparticles and nano-tungsten disulfide are added, ultrasonically vibrated for 1-2 hours, dried and ground to obtain modified nanoparticles.

[0011] By adopting the above technical solution, the ionic liquid is mixed with carbon nanoparticles and nano-tungsten disulfide and then ultrasonicated. The ionic liquid can adhere to the surface of the base oil, wrap the nanoparticles, and generate FeF3, WO3, FeSO4 and other compounds through chemical reactions. Due to the modification of the ionic liquid, the friction film of direct contact between the steel-steel surface can be prevented, and the degree of wear during the friction process is reduced. Moreover, the ionic liquid is a polar liquid, and the cations and anions are adsorbed to the friction surface through the Coulomb force between molecules. The ions in the base oil interact with the long alkyl chain to improve the lubrication performance, thereby also being able to adsorb the nanoparticles and improve the role of the modified nanoparticles in the friction process.

[0012] Optionally, the preparation method of the carbon nanoparticles is as follows: Mix oleylamine, Tween-85, concentrated sulfuric acid and concentrated phosphoric acid, raise the temperature to 150-160°C, keep the temperature for 5-6 hours, filter, wash, freeze-dry, and obtain porous carbon particles; The porous carbon particles were added to DMF, ultrasonicated for 1-2 hours, melamine and triethylamine were added, cyanuric chloride was added after mixing evenly, the mixture was ultrasonicated for 1-2 hours, the temperature was raised to 120-130°C, the reaction was performed for 20-24 hours, the mixture was cooled to room temperature, washed, freeze-dried and ground.

[0013] By adopting the above technical scheme, a mixed acid of sulfuric acid and phosphoric acid is used as the reaction medium to accelerate the dehydration process of Tween-85 molecules. The water produced by the decomposition of the polyoxyethylene group of Tween-85 is rapidly vaporized at 150°C, which may play a role of pore-forming agent in the polymerization and carbonization process. A porous carbon material coated with a long alkyl chain and an ester group with high thermal stability is gradually formed, which can act as a ball bearing under boundary lubrication conditions, play a role of rolling, repairing and polishing, enhance the bearing capacity of the friction film, significantly improve the anti-wear and friction-reducing properties of the base oil, and can also play a good anti- Oxidation; using oleylamine to modify porous carbon materials, oleylamine molecules are covalently grafted to the surface of carbon materials through amide bonds to form oleylamine-modified carbon particles. The oleophilic oleylamine group can keep the porous carbon materials stably dispersed in the base oil; using the solvent method, melamine and cyanuric chloride are used as raw materials to prepare triazine-based two-dimensional covalent organic polymer nanosheets, with porous carbon particles as the core and two-dimensional covalent organic polymer as the shell to construct core-shell carbon nanoparticles. Since the triazine-based two-dimensional covalent organic polymer nanosheet is a nitrogen-rich system, it has Better compatibility, the CH…π interaction formed between it and the base oil also plays a decisive role in the stable dispersion in the base oil. Due to its graphene-like layered structure, triazine-based two-dimensional covalent organic polymer nanosheets can be adsorbed on the bearing surface during the friction process to form a physical adsorption protective film, which effectively reduces the occurrence of friction and wear. The surface lipophilic nanosheets can also effectively prevent the agglomeration of carbon particles and improve the compatibility of carbon particles in oil. The ball effect of carbon microspheres and the adsorption performance of nanosheets can effectively occur, thereby reducing friction and wear. Carbon nanoparticles play the role of micro-ball bearings in rolling friction. Some nanosheets may peel off from the surface of porous carbon particles and adhere to the friction surface to form an adsorption lubricating film, which effectively prevents direct contact between friction surfaces. At the same time, carbon microspheres can still act as micro bearings, thereby maintaining a good lubrication effect for a long time. When the two friction pairs are in contact with each other, the interaction between the rough peaks and the grooves constitutes the friction force during the sliding process. The friction surface load, actual contact area and stress distribution affect the tribological properties. The introduction of nanosheets can increase the actual contact area between contact surfaces in the friction test. The contact pressure distribution is more uniform, which ultimately effectively reduces the friction coefficient and wear volume loss.

[0014] Optionally, the preparation method of the modified polyurea grease is as follows: In a nitrogen atmosphere, fluorinated amino-terminated polydimethylsilane is mixed with tetrahydrofuran, and the temperature is raised to 85-90°C, and then 4,4-diisocyanate dicyclohexylmethane is added. The mixture is kept warm for 20-24 hours, cooled to room temperature, and isophthalaldehyde is added. The mixture is reacted at room temperature for 5-6 hours, and the temperature is raised to 50-60°C, and the mixture is reacted for 1-2 hours. Micro-nano silica mixed particles are added, and the mixture is homogenized by ultrasound to obtain a modified polyurea grease. The mass ratio of fluorinated amino-terminated polydimethylsilane to micro-nano silica mixed particles is 1:0.1-0.2.

[0015] By adopting the above technical scheme, octamethylcyclotetrasiloxane and trifluoropropylcyclotrisiloxane are used to synthesize fluorinated polysiloxane, and polyurea structure and dynamic imine bond are introduced through two-step reaction to prepare fluorinated polysiloxane / polyurea structure with self-healing ability. The structure has low surface energy, and hydrogen bonds and imine bonds construct a double repair network. The hydrogen bond structure brings stronger adhesion to the modified polyurea grease. Since polysiloxane has a certain elasticity, the two ends of the scratch can be quickly brought close. Secondly, the hydrogen bonding effect between the polyurea structures in the polymer makes the two ends of the broken wet more closely connected, so that the modified polyurea grease can quickly self-repair. In addition, the micro-nano silica mixed particles are beneficial to supplement the pores or defects between the modified polyurea grease and the substrate, thereby enhancing the bonding force to a certain extent and improving the viscosity of the grease. In addition, the micro- and nano-scale silica exhibits low surface energy and bionic micro-nano structure in the formed lubricating film, which can make the lubricating film have excellent hydrophobicity and anti-pollutant ability.

[0016] Optionally, the micro-nano silica mixed particles include micron silica and nano silica in a mass ratio of 1:0.2-0.5.

[0017] By adopting the above technical solution, micro-nano structures are constructed in the lubricating film with micron and nano-scale silica, thereby improving the hydrophobicity and foreign body resistance of the lubricating film and enhancing the viscosity and strength of the lubricating film.

[0018] Optionally, the friction modifier is a mixture of cellulose nanocrystals and multi-walled carbon nanotubes modified by ionic liquids, and the specific preparation method is as follows: The multi-walled carbon nanotubes and cellulose nanocrystals are mixed in a mass ratio of 0.5-1:1, nitric acid with a concentration of 60-65wt% is added, ultrasonicated for 1-2h, heated to 100-120°C, condensed and refluxed for 1-2h, filtered, washed until the pH value is 7, and vacuum dried to obtain a carboxylation mixture; The carboxyl compound is dispersed in deionized water, ultrasonically dispersed for 1-2 hours, 1-aminopropyl-3-methylimidazolium bromide is added, rotary evaporated at 50-60°C, reacted at 175-180°C for 12-13 hours under nitrogen protection, cooled to room temperature, deionized water is added, dialyzed for 2-3 days, the dialyzate is rotary evaporated and vacuum dried, and the mass ratio of the carboxylation mixture to 1-aminopropyl-3-methylimidazolium bromide is 1:30-33.

[0019] By adopting the above technical scheme, concentrated nitric acid is used to introduce oxygen-containing groups such as hydroxyl groups on multi-walled carbon nanotubes and cellulose nanocrystals, and ionic liquids can be covalently grafted to the surfaces of carbon nanotubes and cellulose nanocrystals through amide bonds, so that the carbon nanotubes and cellulose nanocrystals can remain suspended and stable in the base oil for a long time due to the electrostatic tension between them, thereby improving the wear reduction and anti-wear effect, and the carbon nanotubes and cellulose nanocrystals can repair and fill the worn surface and form a deposited film to effectively protect the surface and play a role in wear reduction and anti-wear. After the grease is sheared, the soap fibers decompose to form finer fibers dispersed in the base oil, enhancing the viscosity of the oil film and promoting lubrication.

[0020] Optionally, the base oil is selected from at least one of methylphenyl silicone oil, methyl silicone oil, ethyl silicone oil, fluorosilicone oil, PAO10, PAO40, oleic acid and castor oil.

[0021] By adopting the above technical solution, the above synthetic base oils, plant base oils, base silicone oils, etc. all have high lubricity and excellent oxidation stability, and can greatly extend the service life of the bearings.

[0022] Optionally, the surfactant is selected from at least one of lecithin, distearoylphosphatidylcholine and 1,2-dioleoyl lecithin.

[0023] By adopting the above technical solution, the surfactant can improve the compatibility of polyethylene glycol and modified polyurea grease, so that the thickening effect of the lubricant composition is better.

[0024] Optionally, the antioxidant is selected from at least one of alkylated phenylnaphthylamine, zinc dialkyl dithiophosphate and di-tert-butyl-p-cresol; The rust inhibitor is any one of octyl decidyl imidazole, calcium petroleum sulfonate, calcium isooctanoate and zinc isooctanoate.

[0025] By adopting the above technical solution, the antioxidant can effectively inhibit the oxidation reaction of the grease and extend its service life; the rust inhibitor can increase the protection ability of the grease to the bearing.

[0026] In a second aspect, the present application provides a method for preparing a high temperature resistant lubricant composition, using the following technical solution: A method for preparing a high temperature resistant lubricant composition comprises the following steps: mixing a base oil with a thickener, heating to 100-120°C, mixing for 1-2 hours, adding modified nanoparticles, stirring for 2-3 hours, cooling to 80-90°C, adding a rust inhibitor, an antioxidant and a friction modifier, stirring for 0.5-1 hour, degassing and filtering to obtain the lubricant composition.

[0027] In summary, this application has the following beneficial effects: 1. Since the present application adopts bromide-1-hexadecyl-3-methylimidazolium-based ionic liquid to modify the nanoparticles, the ionic liquid and the nanoparticles, together with the lubricating oil, are in close contact with the friction pair surface during the friction process to play a lubricating role. At high temperatures, an oxidation reaction occurs on the friction surface, and the friction surface oxides interact with each other to produce a dense friction film, so that the steel-steel surface is not in direct contact, and the friction performance is further improved. In addition, the ionic liquid can improve the dispersion performance of the nanoparticles in the base oil, enhance the interface effect between the nanoparticles and the base oil, so that the nanoparticles have relatively good dispersion stability and compatibility in the base oil, and improve the extreme pressure wear resistance and the use effect under high temperature.

[0028] 2. In the present application, oleic acid and Tween-85 are preferably used to prepare porous carbon particles, and then a solvent method is used to form triazine-based two-dimensional covalent organic polymer nanosheets on the porous carbon particles, with the porous carbon particles as the core and the two-dimensional covalent nanosheets as the shell, so as to improve the compatibility of the carbon nanoparticles in the base oil, enhance the adsorption force between the carbon nanoparticles and the bearings, reduce wear and friction, and further improve the lubrication effect.

[0029] 3. In the present application, a mixture of cellulose nanocrystals modified by ionic liquids and multi-walled carbon nanotubes is preferably used as a friction modifier, which can be evenly dispersed in the base oil and deposited on the friction surface to form a protective film, thereby increasing the lubrication effect and reducing wear. DETAILED DESCRIPTION

[0030] The following examples further illustrate the present application in detail.

[0031] Preparation Examples 1-7 of Modified Nanoparticles

[0032] Preparation Example 1: 30 g of bromide-1-hexadecyl-3-methylimidazolium ionic liquid was mixed with 300 g of chloroform, heated to 40 ° C and stirred for 30 min, then 22.5 g of carbon nanoparticles and 7.5 g of nano-tungsten disulfide were added, ultrasonically oscillated at a power of 250 W for 2 h, dried at 80 ° C for 24 h, and ground for 30 min to obtain modified nanoparticles. The mass ratio of bromide-1-hexadecyl-3-methylimidazolium ionic liquid to nanoparticles was 1:1. The carbon nanoparticles were selected from Zhejiang Manli Nanotechnology, with a product number of ML-C-N20 and a density of 2.33 g / cm 3Tungsten disulfide is selected from Zhongzhou Alloy Materials in Nangong City, with the product number NO-S-001-1, the average particle size is 300nm, and the density is 7.6g / cm 3 .

[0033] Preparation Example 2: 30 g of bromide-1-hexadecyl-3-methylimidazolyl ionic liquid was mixed with 300 g of chloroform, heated to 50 ° C and stirred for 30 min, then 20 g of carbon nanoparticles and 10 g of nano-tungsten disulfide were added, ultrasonically oscillated at a power of 250 W for 2 h, dried at 80 ° C for 24 h, and ground for 30 min to obtain modified nanoparticles. The mass ratio of bromide-1-hexadecyl-3-methylimidazolyl ionic liquid to nanoparticles was 1:1. The carbon nanoparticles were selected from Zhejiang Manli Nanotechnology, with a product number of ML-C-N20 and a density of 2.33 g / cm 3 Tungsten disulfide is selected from Zhongzhou Alloy Materials in Nangong City, with the product number NO-S-001-1, the average particle size is 300nm, and the density is 7.6g / cm 3 .

[0034] Preparation Example 3: The difference from Preparation Example 1 is that no carbon nanoparticles are added.

[0035] Preparation Example 4: The difference from Preparation Example 1 is that an equal amount of tungsten disulfide is used to replace carbon nanoparticles.

[0036] Preparation Example 5: The difference from Preparation Example 1 is that the carbon nanoparticles are prepared by the following method: (1) Mix 75 ml of oleylamine, 100 ml of Tween-85, 300 ml of concentrated sulfuric acid and 100 ml of concentrated phosphoric acid, heat to 150°C, keep warm for 6 hours, filter, wash with pure water, and freeze-dry at -40°C for 48 hours to obtain porous carbon particles; (2) Add 2 g of porous carbon particles to 600 ml of DMF and ultrasonicate for 2 h. Then add 3.78 g of melamine and 10 ml of triethylamine. After mixing well, add 4.612 g of cyanuric chloride and ultrasonicate for 2 h. Heat to 120 °C and react for 24 h. Cool to room temperature, wash with anhydrous ethanol and deionized water, centrifuge, freeze-dry for 12 h, and grind to nanoscale.

[0037] Preparation Example 6: The difference from Preparation Example 5 is that oleylamine was not added.

[0038] Preparation Example 7: The difference from Preparation Example 5 is that step (2) is not performed, and porous carbon particles are used as carbon nanoparticles.

[0039] Preparation Example 8-12 of Modified Polyurea Grease

[0040] Preparation Example 8: Under a nitrogen atmosphere, 15 g of octamethylcyclotetrasiloxane, 10.56 g of trifluoropropylcyclotrisiloxane, 5.31 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 0.03 g of tetramethylammonium hydroxide-anhydrous compound were mixed, heated to 110° C. in an oil bath, reacted for 12 h, and heated to 170° C. in a vacuum environment, and kept warm for 30 min to synthesize fluorinated amino-terminated polydimethylsiloxane; Under a nitrogen atmosphere, 10g of fluorinated amino-terminated polydimethylsilane was mixed with 50ml of tetrahydrofuran, and the temperature was raised to 90°C, followed by the addition of 7.5g of 4,4-diisocyanate dicyclohexylmethane, which was kept warm for 24h, cooled to room temperature, and 2.5g of isophthalaldehyde was added. The mixture was reacted at room temperature for 5h, raised to 60°C, reacted for 1h, and 2g of micro-nano silica mixed particles were added. The mixture was homogenized by ultrasound to obtain a modified polyurea grease. The micro-nano silica mixed particles included micron silica and nano silica in a mass ratio of 1:0.5. The average particle size of the micron silica was 3μm, which was selected from Qinghe County Chihan Metal, with the item number CH-SiO2-D03. The particle size of the nano silica was 15nm, which was selected from Zhejiang Jingcai Chemical, with the model number JC-SP20.

[0041] Preparation Example 9: Under a nitrogen atmosphere, 15 g of octamethylcyclotetrasiloxane, 10.56 g of trifluoropropylcyclotrisiloxane, 5.31 g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 0.03 g of tetramethylammonium hydroxide-anhydrous compound were mixed, heated to 110° C. in an oil bath, reacted for 12 h, and heated to 170° C. in a vacuum environment, kept warm for 30 min, to synthesize fluorinated amino-terminated polydimethylsiloxane; Under a nitrogen atmosphere, 10g of fluorinated amino-terminated polydimethylsilane was mixed with 50ml of tetrahydrofuran, and the temperature was raised to 80°C, followed by the addition of 7.5g of 4,4-diisocyanate dicyclohexylmethane, and the mixture was kept warm for 20h. The mixture was cooled to room temperature, and 2.5g of isophthalaldehyde was added. The mixture was reacted at room temperature for 6h, and the temperature was raised to 50°C, and the reaction was continued for 2h. 1g of micro-nano silica mixed particles was added, and the mixture was homogenized by ultrasound to obtain a modified polyurea grease. The micro-nano silica mixed particles included micron silica and nano silica in a mass ratio of 1:0.2. The average particle size of the micron silica was 3μm, and the particles were selected from Qinghe County Chihan Metal with the item number CH-SiO2-D03. The particle size of the nano silica was 15nm, and the particles were selected from Zhejiang Jingcai Chemical with the model number JC-SP20.

[0042] Preparation Example 10: The difference from Preparation Example 8 is that no micro-nano silica mixed particles are added.

[0043] Preparation Example 11: The difference from Preparation Example 8 is that an equal amount of micron silicon dioxide is used instead of nano silicon dioxide.

[0044] Preparation Example 12: The difference from Preparation Example 8 is that no fluorinated amino-terminated polydimethylsiloxane is added. Example

[0045] Example 1: A high temperature resistant lubricant composition, the raw materials are shown in Table 1, the base oil is PAO40, and the kinematic viscosity at 40°C is 386 mm 2 / s, 100℃ is 40mm 2 / s, a viscosity index of 147, a pour point of -40°C, a flash point of 295°C, an antioxidant of di-tert-butyl-p-cresol, a rust inhibitor of calcium petroleum sulfonate, a friction modifier of zinc dialkyl dithiophosphate, a thickener comprising polyethylene glycol 200, a modified polyurea grease and a surfactant in a mass ratio of 1:0.5:0.15, the modified polyurea grease being prepared by Preparation Example 8, the surfactant being lecithin, and the modified nanoparticles being brominated-1-hexadecyl-3-methylimidazolium-based ionic liquid-modified nanoparticles, and being prepared by Preparation Example 1.

[0046] The preparation method of the high temperature resistant lubricant composition comprises the following steps: The base oil and the thickener are mixed, heated to 100°C, mixed for 2 hours, the modified nanoparticles are added, stirred for 3 hours, cooled to 90°C, the rust inhibitor, antioxidant and friction modifier are added, stirred for 0.5 hours, degassed and filtered to obtain a lubricant composition.

[0047] Table 1 Amount of raw materials used in the high temperature resistant lubricant composition in Examples 1-3

[0048] Example 2: A high temperature resistant lubricant composition, the raw materials are shown in Table 1, the base oil is PAO40, and the kinematic viscosity at 40°C is 386 mm 2 / s, 100℃ is 40mm 2 / s, a viscosity index of 147, a pour point of -40°C, a flash point of 295°C, an antioxidant of di-tert-butyl-p-cresol, a rust inhibitor of calcium petroleum sulfonate, a friction modifier of zinc dialkyl dithiophosphate, a thickener comprising polyethylene glycol 200, a modified polyurea grease and a surfactant in a mass ratio of 1:0.3:0.1, the modified polyurea grease being prepared by Preparation Example 9, the surfactant being lecithin, and the modified nanoparticles being bromide-1-hexadecyl-3-methylimidazolium-based ionic liquid-modified nanoparticles, and being prepared by Preparation Example 2.

[0049] The preparation method of the high temperature resistant lubricant composition comprises the following steps: The base oil and the thickener were mixed, heated to 120°C, mixed for 1 hour, the modified nanoparticles were added, stirred for 2 hours, cooled to 80°C, the rust inhibitor, antioxidant and friction modifier were added, stirred for 1 hour, degassed and filtered to obtain a lubricant composition.

[0050] Example 3: A high temperature resistant lubricant composition, the raw materials are shown in Table 1, the base oil is PAO40, and the kinematic viscosity at 40°C is 386 mm 2 / s, 100℃ is 40mm 2 / s, a viscosity index of 147, a pour point of -40°C, a flash point of 295°C, an antioxidant of di-tert-butyl-p-cresol, a rust inhibitor of calcium petroleum sulfonate, a friction modifier of zinc dialkyl dithiophosphate, a thickener comprising polyethylene glycol 200, a modified polyurea grease and a surfactant in a mass ratio of 1:0.5:0.15, the modified polyurea grease being prepared by Preparation Example 8, the surfactant being lecithin, and the modified nanoparticles being brominated-1-hexadecyl-3-methylimidazolium-based ionic liquid-modified nanoparticles, and being prepared by Preparation Example 2.

[0051] The preparation method of the high temperature resistant lubricant composition comprises the following steps: The base oil and the thickener are mixed, heated to 100°C, mixed for 2 hours, the modified nanoparticles are added, stirred for 3 hours, cooled to 90°C, the rust inhibitor, antioxidant and friction modifier are added, stirred for 0.5 hours, degassed and filtered to obtain a lubricant composition.

[0052] Example 4: A high temperature resistant lubricant composition, which is different from Example 1 in that the modified polyurea grease is prepared from Preparation Example 10.

[0053] Example 5: A high temperature resistant lubricant composition, which is different from Example 1 in that the modified polyurea grease is prepared from Preparation Example 11.

[0054] Example 6: A high temperature resistant lubricant composition, which is different from Example 1 in that the modified polyurea grease is prepared from Preparation Example 12.

[0055] Example 7: A high temperature resistant lubricant composition, which is different from Example 1 in that the modified nanoparticles are prepared by Preparation Example 5.

[0056] Example 8: A high temperature resistant lubricant composition, which is different from Example 7 in that the modified nanoparticles are prepared by Preparation Example 6.

[0057] Example 9: A high temperature resistant lubricant composition, which is different from Example 7 in that the modified nanoparticles are prepared by Preparation Example 7.

[0058] Example 10: A high temperature resistant lubricant composition, which differs from Example 7 in that the friction modifier is a mixture of cellulose nanocrystals and multi-walled carbon nanotubes modified with ionic liquids, and the specific preparation method is as follows: 10g of multi-walled carbon nanotubes and cellulose nanocrystals were mixed in a mass ratio of 1:1, 600ml of nitric acid with a concentration of 65wt% was added, ultrasonicated at a power of 40kHz for 2h, heated to 100°C, condensed and refluxed for 2h, cooled to room temperature, filtered with a 0.22μm polytetrafluoroethylene filter membrane, washed to a pH of 7, and vacuum dried at 60°C for 12h to obtain a carboxylated mixture, the multi-walled carbon nanotubes were selected from Sichuan Kenye Technology, model KY297C-12, and the cellulose nanocrystals were selected from Xi'an Qiyue Biotechnology, model CNC; Disperse 3 g of carboxyl compound in 300 ml of deionized water, ultrasonicate at a power of 40 kHz for 1 h, add 100 g of 1-aminopropyl-3-methylimidazolium bromide, rotary evaporate at 50 ° C, react at 180 ° C for 12 h under nitrogen protection, cool to room temperature, add 200 ml of deionized water, dialyze for 3 days, change the water 6 times during the period, rotary evaporate the dialysate and vacuum dry it at 60 ° C for 20 h.

[0059] Example 11: A high temperature resistant lubricant composition, which differs from Example 7 in that the friction modifier is a mixture of cellulose nanocrystals and multi-walled carbon nanotubes modified with ionic liquids, and the specific preparation method is as follows: 10g of multi-walled carbon nanotubes and cellulose nanocrystals were mixed in a mass ratio of 1:0.5, 500ml of 60wt% nitric acid was added, ultrasonicated at a power of 50kHz for 1h, heated to 120°C, condensed and refluxed for 1h, cooled to room temperature, filtered with a 0.22μm polytetrafluoroethylene filter membrane, washed to a pH of 7, and vacuum dried at 60°C for 12h to obtain a carboxylated mixture, the multi-walled carbon nanotubes were selected from Sichuan Kenye Technology, model KY297C-12, and the cellulose nanocrystals were selected from Xi'an Qiyue Biotechnology, model CNC; Disperse 3 g of carboxyl compound in 300 ml of deionized water, ultrasonicate at a power of 50 kHz for 2 h, add 90 g of 1-aminopropyl-3-methylimidazolium bromide, rotary evaporate at 60 ° C, react at 175 ° C for 13 h under nitrogen protection, cool to room temperature, add 200 ml of deionized water, dialyze for 2 days, change the water 6 times during the period, rotary evaporate the dialysate and vacuum dry it at 60 ° C for 20 h.

[0060] Example 12: A high temperature resistant lubricant composition, which differs from Example 10 in that no cellulose nanocrystals are added.

[0061] Example 13: A high temperature resistant lubricant composition, which differs from Example 10 in that cellulose nanocrystals are used in equal amounts to replace multi-walled carbon nanotubes.

[0062] Example 14: A high temperature resistant lubricant composition, which differs from Example 10 in that 1-aminopropyl-2-methylimidazolium bromide is not used for treatment, and a carboxyl compound is used as a friction modifier.

[0063] Comparative Example

[0064] Comparative Example 1: A high temperature resistant lubricant composition, which differs from Example 1 in that the nanoparticles are not modified by bromide-1-hexadecyl-3-methylimidazolium ionic liquid, and a mixture of carbon nanoparticles and nano-tungsten disulfide in a mass ratio of 3:1 is used as the nanoparticles.

[0065] Comparative Example 2: A high temperature resistant lubricant composition, which is different from Example 1 in that the modified nanoparticles are prepared by Preparation Example 3.

[0066] Comparative Example 3: A high temperature resistant lubricant composition, which is different from Example 1 in that the modified nanoparticles are prepared by Preparation Example 4.

[0067] Comparative Example 4: A high temperature resistant lubricant composition, which is different from Example 1 in that polyethylene glycol is not added to the thickener.

[0068] Comparative Example 5: A high temperature resistant lubricant composition, which is different from Example 1 in that no modified polyurea grease is added to the thickener.

[0069] Comparative Example 6: A high temperature resistant lubricant composition, which is different from Example 1 in that the thickener is dodecyl hydroxystearic acid.

[0070] Performance testing

[0071] The lubricant composition was prepared according to the methods in the examples and comparative examples, and the performance was tested according to the following methods. The test results are recorded in Table 2.

[0072] 1. Working cone penetration: According to ASTM D217-2017 standard, the grease sample is placed in a standard working device. At 25°C, after 60 shears, the measured cone penetration is 0.1mm.

[0073] 2. Oxidation stability: Determine according to SH / T 0193-2008 standard. Put a certain amount of grease into an oxygen bomb filled with oxygen pressure and undergo oxidation at 100°C. After 30 hours, the oxidation stability of the grease is determined by the corresponding oxygen pressure drop.

[0074] 3. Viscosity: Test according to GB / T0681-1999 “Determination of apparent viscosity of lubricating grease”.

[0075] 4. Oil film strength: The test was conducted on a MRS-10A four-ball extreme pressure tester at a speed of 1450r / min for 10s. The test ball was a national grade II standard GCr bearing steel ball with a diameter of 12.7mm and a hardness of HRC64-66. The oil film strength P of the grease at 200°C was tested. B value.

[0076] 5. Wear spot diameter: The test was carried out in accordance with NB / SH / T0189-2017 "Determination of Anti-wear Performance of Lubricating Oils by Four-Ball Method", with an experimental speed of 1200 r / min, a temperature of 75°C, a wear time of 30 min, and an experimental load of 196 N.

[0077] Table 2 Performance test results of high temperature resistant lubricant composition

[0078] Combining Examples 1-3 and the data in Table 2, it can be seen that the modified nanoparticles prepared in Preparation Examples 1 and 2, and the modified polyurea greases prepared in Examples 8 and 9 in Examples 1-3, show that the high temperature resistant lubricant compositions prepared in Examples 1-3 have higher working penetration and viscosity, and have good oxidation stability, high temperature oil film strength, small wear spot diameter, good high temperature resistance, and strong lubrication effect.

[0079] In Example 4 and Example 5, modified polyurea grease prepared in Preparation Example 10 and Preparation Example 11 were used respectively. Compared with Preparation Example 8, no micro-nano silica mixed particles were added in Preparation Example 10, and only micron silica was used in Preparation Example 11. The oil film strength of the lubricant composition prepared in Example 4 and Example 5 was reduced, the wear spot diameter was increased, and the high temperature resistance and lubrication ability were reduced.

[0080] In Example 6, the modified polyurea grease prepared in Preparation Example 12 was used. Compared with Preparation Example 8, no fluorinated amino-terminated polydimethylsiloxane was added. The viscosity of the lubricant composition decreased, the cone penetration increased, but the oil film strength deteriorated.

[0081] In Example 7, the modified nanoparticles prepared in Preparation Example 1 are used. Compared with Preparation Example 1, the carbon material is modified using oleylamine and coated with triazine-based two-dimensional covalent organic polymer nanosheets. The obtained carbon nanoparticles have higher wear resistance and lubrication effects, and have stronger oil film strength at high temperatures.

[0082] Compared with Example 7, Examples 8 and 9 use the modified nanoparticles prepared in Preparation Examples 6 and 7, respectively. No oleylamine is added in Preparation Example 6, and no melamine, cyanuric chloride, etc. are used in Preparation Example 7. As can be seen from Table 2, the high-temperature lubricity of the lubricant compositions prepared in Examples 8 and 9 is reduced.

[0083] Compared with Example 7, Examples 10 and 11 use a mixture of cellulose nanocrystals modified with ionic liquid and multi-walled carbon nanotubes as a friction modifier. Table 2 shows that the lubricant compositions prepared in Examples 10 and 11 have reduced wear spot diameters, improved high temperature resistance, and increased working cone penetration.

[0084] In Example 12, cellulose nanocrystals were not added, and in Example 13, cellulose nanocrystals were used instead of multi-walled carbon nanotubes. Compared with Example 10, the viscosity of the lubricant composition in Example 12 was reduced, and the viscosity of the lubricant composition in Example 13 was increased, and the working cone penetration was reduced.

[0085] In Example 14, 1-aminopropyl-2-methylimidazolium bromide was not used to modify the carboxyl compound, and the carboxyl compound was used as a friction modifier. Compared with Example 10, the lubricating ability of the lubricant composition prepared in Example 14 decreased.

[0086] In Comparative Example 1, no 1-hexadecyl-3-methylimidazolium bromide ionic liquid modification was used, and only carbon nanoparticles and nano-tungsten disulfide were used. The data in Table 2 show that the working cone penetration of the lubricant composition prepared in Comparative Example 1 is reduced, the oil film strength is reduced, and the lubrication effect is deteriorated.

[0087] In Comparative Example 2, the modified nanoparticles prepared in Preparation Example 3 were used, and in Comparative Example 3, the modified nanoparticles prepared in Preparation Example 4 were used. Compared with Preparation Example 1, no carbon nanoparticles were added in Preparation Example 3, and tungsten disulfide was used instead of carbon nanoparticles in Preparation Example 4. The data in Table 2 show that the viscosity of the lubricant composition prepared in Comparative Example 2 is reduced, the working cone penetration is increased, and the fluidity is enhanced, but the oxidation stability is reduced, the oil film strength is reduced, the wear spot diameter is increased, and the lubrication effect is reduced. The lubricant composition prepared in Comparative Example 3 has little change in viscosity, but its oil film strength at 200°C is reduced, its high temperature resistance is weakened, the wear spot diameter is increased, and the lubrication effect is weakened.

[0088] Compared with Example 1, Comparative Example 4 does not add polyethylene glycol, and compared with Example 1, Comparative Example 5 does not add modified polyurea grease. Compared with Example 1, the lubricant compositions prepared in Comparative Examples 4 and 5 have a slightly lower viscosity and are difficult to form a dense lubricating film on the substrate, so the oil film strength and wear spot diameter are both reduced.

[0089] In Comparative Example 6, dodecyl hydroxystearic acid is used as a thickener. Compared with Example 1, the working cone penetration of the lubricant composition prepared in Comparative Example 6 decreases, the viscosity decreases, and the performance of the lubricant decreases.

[0090] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high temperature resistant lubricant composition, characterized in that: The invention comprises the following raw materials in parts by weight: 90-110 parts of base oil, 30-35 parts of thickener, 2-3.5 parts of modified nanoparticles, 0.5-1.5 parts of antioxidant, 1-3 parts of rust inhibitor and 0.5-1 parts of friction modifier; The thickener comprises polyethylene glycol, modified polyurea grease and surfactant in a mass ratio of 1:0.3-0.5:0.1-0.15; The modified nanoparticles are bromide-1-hexadecyl-3-methylimidazolium-based ionic liquid modified nanoparticles, and the nanoparticles include carbon nanoparticles and nano-tungsten disulfide in a mass ratio of 2-3:

1.

2. The high temperature resistant lubricant composition according to claim 1, characterized in that: The preparation method of the modified nanoparticles is as follows: The bromide-1-hexadecyl-3-methylimidazolium ionic liquid is mixed with chloroform, the temperature is raised to 40-50° C., and the mixture is stirred evenly. Then, carbon nanoparticles and nano-tungsten disulfide are added, ultrasonically vibrated for 1-2 hours, dried and ground to obtain modified nanoparticles.

3. The high temperature resistant lubricant composition according to claim 2, characterized in that: The preparation method of the carbon nanoparticles is as follows: Mix oleylamine, Tween-85, concentrated sulfuric acid and concentrated phosphoric acid, raise the temperature to 150-160°C, keep the temperature for 5-6 hours, filter, wash, freeze-dry, and obtain porous carbon particles; The porous carbon particles were added to DMF, ultrasonicated for 1-2 hours, melamine and triethylamine were added, cyanuric chloride was added after mixing evenly, the mixture was ultrasonicated for 1-2 hours, the temperature was raised to 120-130°C, the reaction was performed for 20-24 hours, the mixture was cooled to room temperature, washed, freeze-dried and ground.

4. The high temperature resistant lubricant composition according to claim 1, characterized in that: The preparation method of the modified polyurea grease is as follows: In a nitrogen atmosphere, fluorinated amino-terminated polydimethylsilane is mixed with tetrahydrofuran, and the temperature is raised to 85-90°C, and then 4,4-diisocyanate dicyclohexylmethane is added. The mixture is kept warm for 20-24 hours, cooled to room temperature, and isophthalaldehyde is added. The mixture is reacted at room temperature for 5-6 hours, and the temperature is raised to 50-60°C, and the mixture is reacted for 1-2 hours. Micro-nano silica mixed particles are added, and the mixture is homogenized by ultrasound to obtain a modified polyurea grease. The mass ratio of fluorinated amino-terminated polydimethylsilane to micro-nano silica mixed particles is 1:0.1-0.

2.

5. The high temperature resistant lubricant composition according to claim 4, characterized in that: The micro-nano silicon dioxide mixed particles include micron silicon dioxide and nano silicon dioxide in a mass ratio of 1:0.2-0.

5.

6. The high temperature resistant lubricant composition according to claim 1, characterized in that: The friction modifier is a mixture of cellulose nanocrystals and multi-walled carbon nanotubes modified by ionic liquids, and the specific preparation method is as follows: The multi-walled carbon nanotubes and cellulose nanocrystals are mixed in a mass ratio of 0.5-1:1, nitric acid with a concentration of 60-65wt% is added, ultrasonicated for 1-2h, heated to 100-120°C, condensed and refluxed for 1-2h, filtered, washed until the pH value is 7, and vacuum dried to obtain a carboxylation mixture; The carboxyl compound is dispersed in deionized water, ultrasonically dispersed for 1-2 hours, 1-aminopropyl-3-methylimidazolium bromide is added, rotary evaporated at 50-60°C, reacted at 175-180°C for 12-13 hours under nitrogen protection, cooled to room temperature, deionized water is added, dialyzed for 2-3 days, the dialyzate is rotary evaporated and vacuum dried, and the mass ratio of the carboxylation mixture to 1-aminopropyl-3-methylimidazolium bromide is 1:30-33.

7. The high temperature resistant lubricant composition according to claim 1, characterized in that: The base oil is selected from at least one of methylphenyl silicone oil, methyl silicone oil, ethyl silicone oil, fluorosilicone oil, PAO10, PAO40, oleic acid and castor oil.

8. The high temperature resistant lubricant composition according to claim 1, characterized in that: The surfactant is selected from at least one of lecithin, distearoylphosphatidylcholine and 1,2-dioleoyl lecithin.

9. The high temperature resistant lubricant composition according to claim 1, characterized in that: The antioxidant is selected from at least one of alkylated phenylnaphthylamine, zinc dialkyl dithiophosphate and di-tert-butyl-p-cresol; The rust inhibitor is any one of octyl decidyl imidazole, calcium petroleum sulfonate, calcium isooctanoate and zinc isooctanoate.

10. The method for preparing the high temperature resistant lubricant composition according to any one of claims 1 to 9, characterized in that: The following steps are involved: The base oil and the thickener are mixed, heated to 100-120°C, mixed for 1-2 hours, the modified nanoparticles are added, stirred for 2-3 hours, cooled to 80-90°C, the rust inhibitor, antioxidant and friction modifier are added, stirred for 0.5-1 hour, degassed and filtered to obtain a lubricant composition.

Citation Information

Patent Citations

  • Heavy-load exposed gear graphene lubricating grease and preparation method thereof

    CN119529920A

  • Lubricating grease, useful as e.g. antifriction bearing grease, high temperature grease and friction bearing grease, comprises base oil, thickening agent, inorganic material and optionally further more usual additives

    DE102004021812A1

  • A method of reducing friction and wear between surfaces under a high load condition

    US20150315514A1

Cited By

  • Giant electrorheological fluid, preparation method and application of giant electrorheological fluid in rigid-flexible matrix digital controllable intelligent material

    CN121538011A

  • Giant electro-rheological fluid, preparation method and application thereof in rigid-flexible matrix digital controllable intelligent material

    CN121538011B